PENGARUH MOTIVASI KERJA, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA GURU DI SEKOLAH MENENGAH ATAS NEGERI SE-KABUPATEN HALMAHERA TIMUR PROPINSI MALUKU UTARA (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The Influence of Work Motivation, Organizational Culture and Leadership Style on Teacher Performance of High School in The Country East Halmahera Regency, North Maluku Province. The purpose of this study is: (1) to determine the effect of job motivation, organizational culture and leadership style on teacher performance, (2) to determine the effect of motivation on the job performance of teachers, (3) the influence of organizational culture on the performance of teachers and (4) to know the influence of leadership style on teacher performance. This research is quantitative. Population in this study were all high school teachers in the Country as Eastern Halmahera Regency, North Maluku province, amounting to 92 people. Data collection using a questionnaire which includes teacher performance , motivation, organizational culture and leadership style . Data analysis technique used is multiple regression analysis to determine the effect of independent variables on the dependent variables simultaneously. The results showed that job motivation, organizational culture and leadership style simultaneously and partially positive influence on the performance of high school teachers in the Country East Halmahera Regency North Maluku Province, then the hypothesis is proven true. In the determination coefficient test showed variable work motivation, organizational culture and leadership style on teacher performance by 28.1% while the remaining 71, 9% is explained by other variables outside of this study. The magnitude of the effective contribution that can affect the performance of teachers to work motivation by 8.5%, amounting to 5.4% of organizational culture and leadership style was 14.2%.